Evaluation of Samsat Virtu Tax Payment Service Innovations in Increasing Original Regional Income in Bengkulu City - Heru Purnawan; Suwantoro, Kadek; Dani, Rahiman; Henny Aprianty (PERSPEKTIF, 2024)
The aim of this research is twofold, namely trying to determine the implementation and evaluate innovations in Samsat Virtu motor vehicle tax payment services to increase regional income. With a research focus on motor vehicle tax (PKB), which is one of the elements of regional income that has a high contribution. Implementation Theory of policy implementation according to Van Meter and Van Horn(Budi Winarno, 2016)where 6 aspects are examined, namely: 1) policy standards and targets, 2) policy resources, 3) communication between organizations, 4) characteristics of the implementing agency/attitude of the implementer and 5) social, political and economic conditions, and the evaluation theory used namely policy evaluation theory from William N. Dunn with indicators 1) Value focus, 2) Interdependence of value facts, and 3) Present and past orientation. The type of research used in this research is descriptive qualitative. Where the author participated in the field, observed what was happening, carried out direct analysis of the document findings, and prepared a detailed report of the findings. The research was conducted at the UPTD Samsat City of Bengkulu, which was carried out in May 2023. From the results of the research it is known that the implementation of virtual Samsat public service innovation in Bengkulu City has policy standards and targets, financial resources and time, coordination between organizations, characteristics namely equipped with SOPs, and supported by the attitude of the innovation implementer which is equipped with knowledge, understanding and deepening as well as services that prioritize 5S culture, in addition to being supported by socio-political and economic conditions that are conducive to the implementation of service innovation. Inhibiting factors in the implementation of samsat virtu innovation such as Weather factors, internet access, and regular servicing of hardware and software have been anticipated by the Bengkulu City Samsat so that Samsat Virtu innovation services can continue to be carried out well.